STRATEGIC PLANNING OF ISLAMIC EDUCATION IN REALIZING THE VISION AND MISSION OF ISLAMIC EDUCATION INSTITUTIONS - Muchlisin, Muchlisin; Fahmi, Nurkafidz Nizam (STKIP Pesisir Selatan, 2025)
The purpose of this study is to analyze the strategic planning of Islamic education implemented at SMP Plus Darussalam Banyuwangi in realizing the vision and mission of the institution, with a focus on the integration of religious values and local culture.This research uses a qualitative approach with a case study design to analyze the strategic planning of Islamic education at SMP Plus Darussalam Banyuwangi. Data sources include in-depth interviews with principals, teachers, parents and stakeholders, direct observation at the school, and documentation such as strategic planning and annual reports. Data were thematically analyzed to identify patterns and themes that support or hinder strategic planning. This research aims to provide a holistic understanding of the implementation of strategic planning in Islamic education. The results of this study show that SMP Plus Darussalam Banyuwangi successfully integrates religious values, local culture and technology in educational strategic planning. The main focus on character education shapes students' noble morals according to Islamic teachings, while the active involvement of stakeholders ensures the relevance of the school's vision and mission to local needs. The flexibility of the curriculum allows for adaptation to the times without compromising traditional values.